2019
DOI: 10.1002/art.40692
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Knee Osteoarthritis With Obesity, Sarcopenic Obesity, and Sarcopenia

Abstract: In this large longitudinal cohort, we found body composition based obesity and sarcopenic obesity but not sarcopenia, to be associated with knee OA risk. Weight loss strategies for knee OA should focus on obesity and sarcopenic obesity. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
2
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(97 citation statements)
references
References 18 publications
(27 reference statements)
3
74
2
6
Order By: Relevance
“…Sarcopenic obesity, which is characterized by the combination of obesity and sarcopenia (age-related muscle loss and physical dysfunction), is associated with a higher risk of radiographic knee OA, relative to individuals in the non-sarcopenia obesity group, demonstrated in a cross-sectional study based on 2893 individuals [ 82 ]. Interestingly, a recent longitudinal study based on 1653 patients showed an association between sarcopenic obese women and increased risk of radiographic knee OA, however this was not seen in men, suggesting that the effect of muscle dysfunction on obesity-related OA development may be related to gender [ 83 ].…”
Section: Mechanical Stress As a Key Pathological Factor In Obesity-rementioning
confidence: 99%
“…Sarcopenic obesity, which is characterized by the combination of obesity and sarcopenia (age-related muscle loss and physical dysfunction), is associated with a higher risk of radiographic knee OA, relative to individuals in the non-sarcopenia obesity group, demonstrated in a cross-sectional study based on 2893 individuals [ 82 ]. Interestingly, a recent longitudinal study based on 1653 patients showed an association between sarcopenic obese women and increased risk of radiographic knee OA, however this was not seen in men, suggesting that the effect of muscle dysfunction on obesity-related OA development may be related to gender [ 83 ].…”
Section: Mechanical Stress As a Key Pathological Factor In Obesity-rementioning
confidence: 99%
“…According to a 2016 data, there were 43.2 million men and 46.4 million women in China, and the number of obese people exceeded that of the USA, ranking first in the world [ 2 ]. As a health problem, obesity is more common in elderly people and is associated with many diseases, including osteoarthritis (OA) [ 3 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Obesity may contribute to OA pathogenesis in two ways, by increasing joint load and mechanical wear of the joints, and by promoting systemic and local inflammation. Body composition studies demonstrated a direct association of obesity with the risk of knee OA, suggesting that weight loss strategies for knee OA should focus on reducing excess fat tissue [2,3]. Partial or full IFP resection has been used to reduce knee pain resulting from IFP inflammation and impingement during total knee arthroplasty [28].…”
Section: Adipokine Adiponectinmentioning
confidence: 99%
“…Obesity is a common metabolic syndrome caused by excess fat accumulation in the body due to disorders of fat metabolism. Previous research has demonstrated a strong association between knee OA and obesity [1][2][3][4][5]. Obesity not only causes increased weight bearing by the joint but also enhances adipokine production by the adipose tissue, thereby contributing to inflammatory or autoimmune diseases [6,7].…”
Section: Introductionmentioning
confidence: 99%